2019
DOI: 10.1002/1873-3468.13516
|View full text |Cite
|
Sign up to set email alerts
|

MEF2C/miR‐133a‐3p.1 circuit‐stabilized AQP1 expression maintains endothelial water homeostasis

Abstract: Aquaporin 1 (AQP1) plays an important role in endothelial functions and is regulated by MEF2C. However, how AQP1 level is stabilized to maintain endothelial water homeostasis is still not clear. Here, we show that AQP1 expression is significantly upregulated by MEF2C transcriptionally and inhibited by miR‐133a‐3p.1 post‐transcriptionally. Meanwhile, MEF2C activates the expression of miR‐133a1. Simultaneous overexpression of MEF2C and miR‐133a‐3p.1 suppresses the aptitude of changes in AQP1 expression caused by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In the other tumors, including ovarian cancer ( 23 ), osteosarcoma ( 24 ), breast cancer ( 40 ) and melanoma ( 41 ), knockdown of AQP1 inhibits cell proliferation and invasion. Notably, the association between miR-133a-3p and AQP1 has also been described in endothelial cells ( 28 ). Based on these previous studies, it was thus speculated that miR-133a-3p expression also influences AQP1 not only in non-malignant endothelial cells but also in CRC.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the other tumors, including ovarian cancer ( 23 ), osteosarcoma ( 24 ), breast cancer ( 40 ) and melanoma ( 41 ), knockdown of AQP1 inhibits cell proliferation and invasion. Notably, the association between miR-133a-3p and AQP1 has also been described in endothelial cells ( 28 ). Based on these previous studies, it was thus speculated that miR-133a-3p expression also influences AQP1 not only in non-malignant endothelial cells but also in CRC.…”
Section: Discussionmentioning
confidence: 91%
“…Notably, the expression of AQP1 is an independent poor prognostic factor for stage II and III CRC ( 26 , 27 ), but the biological function of AQP1 in CRC remains undetermined. Notably, a recent study by Jiang et al ( 28 ) illustrated that the myocyte-specific enhancer factor 2C and miR-133a-3p regulatory circuit could maintain the homeostasis and physiological function of AQP1 in endothelial cells. Nevertheless, whether AQP1 is a target gene of miR-133a-3p in CRC cell functions still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Aortic endothelial cells from AQP1‐knockout mice have greatly reduced migratory and vessel formation abilities [9,12]. The expression level or activity of AQP1 in promoting angiogenesis is regulated by Mef2C and miR‐131a1‐3p [12,30], estrogen [13], or hypoxia [31]. AQP1 has been shown to regulate the migration of many types of cancer cells [5–7,9].…”
Section: Discussionmentioning
confidence: 99%
“…Aquaporins in the transcellular pathway are vital to the pathways involved in the regulation of vascular endothelial permeability. 29 Zhang et al 30 found that reducing AQP3 expression increases the permeability of vascular endothelial cells. According to Jiang et al 31 the p38/MAPK signaling pathway can increase the expression of claudin3 and occludin.…”
Section: Introductionmentioning
confidence: 99%